A novel wide bandgap conjugated polymer (2.0 eV) based on bithiazole for high efficiency polymer solar cells. (April 2017) - Guo, Bing; Li, Wanbin; Guo, Xia; Meng, Xiangyi; Ma, Wei; Zhang, Maojie; Li, Yongfang
Abstract: An efficient wide bandgap conjugated polymer (PTZ6) based on alkoxylphenyl substituted benzodithiophene as donor unit and bithiazole as acceptor unit was developed for polymer solar cells (PSCs). The polymer exhibited a wide bandgap of 2.0 eV with strong absorption in the range of 300–620 nm, and a low-lying highest occupied molecular orbital (HOMO) energy level of −5.36 eV. The PSCs based on PTZ6: PC71 BM show a PCE of 8.1% with a V oc of 0.96 V, a J sc of 10.9 mA cm −2 and a high FF of 76.7%, which is among the highest values for the fullerene PSCs based on conjugated polymer donors with bandgap near to 2.0 eV. Moreover, for this blend system, the photovoltaic performance of the devices changes little when the active layer thickness increases from 90 nm to 220 nm. More importantly, the non-fullerene PSCs based on PTZ6: ITIC exhibit a PCE of 10.3% with a high V oc of 1.01 V, which should be the best value for the non-fullerene PSCs with the E loss less than 0.6 eV to date. Our results indicate that PTZ6 is a promising wide bandgap polymer donor for the photovoltaic application in PSCs. Graphical abstract: A novel wide bandgap conjugated polymer PTZ6 with an E g of 2.0 eV is designed and synthesized for photovoltaic application. PSCs based on PTZ6: PC71 BM and PTZ6: ITIC blend films exhibit high PCEs of up to 8.1% and 10.3%, respectively, under the illumination of AM 1.5 G, 100 mW cm −2 . Highlights: The non-fullerene PSCs based on PTZ6: ITIC exhibit a PCE of 10.3%. The PSCs based on PTZ6: PC71BM show a PCE of 8.1%. A novel wide bandgap conjugated polymer (PTZ6) with 2.0 eV was synthesized.